Uniparental Genetic Analyses Reveal Multi-Ethnic Background of Dunhuang Foyemiaowan Population (220–907 CE) With Typical Han Chinese Archaological Culture - Xiong, Jianxue; Tao, Yichen; Ben, Minxi; Yang, Yishi; Du, Panxin; Allen, Edward; Wang, Hui; Xu, Yiran; Yu, Yao; Meng, Hailiang; Bao, Haoquan; Zhou, Boyan; et al. (Frontiers in Ecology and Evolution, 2022)
The relationship between archaeological culture and ethnicity is invariably complex. This is especially the case for periods of national division and rapid inter-ethnic exchange, such as the Northern and Southern Dynasties and Sixteen Kingdoms era (420-589 CE) in China. Going by tomb shape and grave goods, the Foyemiaowan cemetery at Dunhuang exhibits a typical 3rd-7th century (Cao-Wei through Tang) Han style. Despite this, the ethnic makeup of the Foyemiaowan population has remained unclear. We therefore analyzed 485 Y-chromosomal SNPs and entire mitochondrial genomes of 34 Foyemiaowan samples. Our study yielded the following discoveries: 1) principal analysis revealed that the Foyemiaowan population was closely clustered with Tibeto-Burman populations on the paternal side and close to Mongolic-speaking populations on the maternal side; 2) lineage comparisons at the individual level showed that the Foyemiaowan population consisted of primarily Tibeto-Burman and Han Chinese related lineages (Oα-M117, 25%；Oβ-F46, 18.75%), partially Altaic speaking North Eurasian lineages (N-F1206,18.75%) and a slight admixture of southern East Asian lineages (O1b1a2-Page59, 6.25%; O1b1a1-PK4, 3.13%). Similarly, the maternal gene pool of Foyemiaowan contained northern East Asian (A, 4.17%; CZ, 16.67%; D, 20.83%; G, 4.17%; M9, 4.17%), southern East Asian (B, 12.51%; F, 20.83%) and western Eurasian (H, 4.17%; J, 4.17%) related lineages; 3) we discovered a relatively high genetic diversity among the Foyemiaowan population (0.891) in our ancient reference populations, indicating a complex history of population admixture. Archaeological findings, stable isotope analysis and historical documents further corroborated our results. Although in this period China’s central government had relinquished control of the Hexi Corridor and regional non-Han regimes became the dominant regional power, Foyemiaowan’s inhabitants remained strongly influenced by Han culture.